2016
DOI: 10.1111/dth.12420
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous improvement and worsening of vitiligo lesions during the course of NB-UVB phototherapy; vitiligo may not act as one unit

Abstract: Re-pigmentation and stabilization are the two ultimate goals of any re-pigmenting plan designed for vitiligo management. Furthermore, whether the improvement of some vitiligo lesions could be considered a guarantee for a similar response and/or stabilization of the rest of the lesions or not, remains to be clarified. To evaluate the behavior of non-segmental vitiligo (NSV), while on narrow band-ultraviolet B (NB-UVB) phototherapy. 25 patients with stable generalized NSV were included and received NB-UVB twice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…We noticed activity in some lesions in Group 1 on both sides in some patients, while it occurred on one side only in other patients. This result could be explained by Anbar, Abdel‐Rahman, Hegazy, El‐Khayyat, and Ragaie (), who reported that vitiligo at many times may not act as one unit. Moreover, the improvement of some vitiligo lesions cannot be considered a guarantee for a similar response and/or stabilization of the rest of the lesions (Anbar et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We noticed activity in some lesions in Group 1 on both sides in some patients, while it occurred on one side only in other patients. This result could be explained by Anbar, Abdel‐Rahman, Hegazy, El‐Khayyat, and Ragaie (), who reported that vitiligo at many times may not act as one unit. Moreover, the improvement of some vitiligo lesions cannot be considered a guarantee for a similar response and/or stabilization of the rest of the lesions (Anbar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This result could be explained by Anbar, Abdel‐Rahman, Hegazy, El‐Khayyat, and Ragaie (), who reported that vitiligo at many times may not act as one unit. Moreover, the improvement of some vitiligo lesions cannot be considered a guarantee for a similar response and/or stabilization of the rest of the lesions (Anbar et al, ). The vitiligo global issue consensus conference statement was that individual lesional stability does not necessarily reflect global stability of the disease (Ezzedine et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This early detection of activity and the subsequent change in the treatment policy may ultimately change the final outcome of treatment (Anbar, Abdel-Rahman, Hegazy, El-Khayyat, & Ragaie, 2017). However, vitiligo at many times may not act as one unit.…”
Section: Com M En Tmentioning
confidence: 99%
“…Vitiligo is likely to represent a spectrum of many different disorders (Ezzedine et al, ; Hercogová, Schwartz, & Lotti, ; Lotti & D'Erme, ; Rodrigues et al, ). The complex etiopathogenesis with overlapping inflammatory processes and the interplay of multiple factors, often acting in opposite directions is still poorly understood (Anbar, Abdel‐Rahman, Hegazy, El‐Khayyat, & Ragaie, ). An obscure trigger event is thought to cause a chain of events in genetically susceptible individuals (Spritz, ).…”
Section: Introductionmentioning
confidence: 99%